Achieving wide-angle mechanical beam steering in Ka-band with low-profile transmit-array antennas - Matos, S.; Vaquero, Á. F.; Arrebola, M.; Costa, J. R.; Felício, J.; Fernandes, C.; Fonseca, N. J. G. (2023 17th European Conference on Antennas and Propagation (EuCAP), 2023)
Beam scanning and high gain are fundamental requisites for antennas operating at millimeter wave, where many 5G and satellite-on-the-move applications are emerging. Mechanical beam steering using Transmit-arrays (TAs) has been proposed as a viable alternative to the more costly and complex electronic-based solutions. As a spatially fed array, TAs operate with a minimal focal length, distance between the primary source and the radiating aperture, which impacts on the overall size of the antenna. The focal length also limits the maximum scanning range that can be achieved through a linear displacement of the primary source parallel to the aperture (a common mechanical scanning approach using TAs). In this work, an iterative method for optimizing the unit cells distribution in the aperture for low F/D (focal length over aperture ratio) is presented. This approach allows extending the scanning range of the common unifocal TA phase distribution. To validate the proposed method, a TA with F=50 mm and inplane dimensions 195x145 mm (F/D = 0.34) operating at Kaband (30 GHz) was designed. The full-wave results show that this antenna as a 3 dB scanning range of [-59°, 59°], with a maximum gain of 26.3 dBi at 30 GHz and SLL < -11.7 dB.